Night Cream Containing Melatonin, Carnosine and Helichrysum italicum Extract Helps Reduce Skin Reactivity and Signs of Photodamage: Ex Vivo and Clinical Studies - Corinne Granger (Dermatology and Therapy, 2020)
Abstract Introduction Extrinsic factors, such as solar radiation and urban pollution, cause damage that alters the structure, function and appearance of skin. The aim of this study was to determine the ability of a night cream containing melatonin, carnosine and Helichrysum italicum extract (referred to here as Night Cream) to reduce extrinsic skin damage, and to evaluate the efficacy of this Night Cream to reduce clinical signs of age and photodamage under normal conditions of use. Methods Recovery from extrinsic damage was assessed by exposing human skin explants to ultraviolet (UV) A, infrared light, blue light or pollution and then treating the stress-exposed explants with Night Cream. Markers of oxidative stress were examined by immunohistochemistry. Anti-aging and calming properties were determined in four single-center, open-label trials involving 117 individuals. Subjects applied Night Cream to their face once nightly for up to 12 weeks. Improvements in clinical signs of age and photodamage, and reduction of lactic acid-induced stinging were evaluated by investigator assessment and subject self-assessment. Results Night Cream significantly reduced oxidative stress in human skin ex vivo. Clinically, hydration (+ 64.4%; p < 0.05) and transepidermal water loss (TEWL) values (− 10.0%; p < 0.05) were improved within 1 h of use. Wrinkle counts were reduced by up to 18.9% (p < 0.05), and brown and UV spot numbers by 5.5% (p < 0.05) and 13.2% (p < 0.05), respectively. Lactic acid-induced stinging was significantly reduced within 7 days of use, with 86.7% of subjects reporting that their skin felt calmer. Conclusion These findings suggest that Night Cream reduces skin damage caused by environmental factors and that its nightly use can improve clinical signs of aging with additional skin calming benefits.